An Investigation of the "Green World Escape" in Three Victorian Plays - Mohammed, Jwan Adil (Journal of Tikrit University for Humanities, 2023)
Urban gardens, parks, and conservatories had grown popular by the late nineteenth century and were now widely available to the public on a cultural and social level. Creating natural areas inside cities merged the rural and urban sectors into a single locale. In order to examine the "green world" experience in Victorian theater, three plays by three British playwrights namely Arthur Wing Pinero, Henry Arthur Jones, and Oscar Wilde from the second half of the nineteenth century have been chosen for this study. The plays span farces, fantasy, and melodrama, presenting many viewpoints on the idea of escapism along with the discovery of and yearning for other worlds. By analyzing the dreams and experiences of the alternate universe, it is feasible to understand Victorian views about the landscape and its role as a respite from urban or industrial commercial centers. This can assist to spark a discussion about characters’ desires for escape and the circumstances that drive them to seek tranquility in rural locations. The protagonists’ otherworldly experiences inside the alternate worlds may be examined if it is obvious what they are trying to get away from. After knowing what happens in the green world, it is possible to examine how often characters are able to go through difficult situations.